2018
DOI: 10.1002/anie.201811362
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Calibrated Analysis of the Electronic Structure of CuO+: Implications for Reactivity

Abstract: The CuO + core is ac entral motif of reactive intermediates in copper-catalysed oxidations occurring in nature.T he high reactivity of CuO + stems from aw eak bonding between the atoms,w hich cannot be described by asimple classical model. To obtain the correct picture,wehave investigated the acetonitrile-ligated CuO + ion using neontagging photodissociation spectroscopya t5K. The spectra feature complex vibronic absorption progressions in NIR and visible regions.E mploying Franck-Condon analyses,w e derived l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 37 publications
2
40
1
Order By: Relevance
“…Markedly, the frequency of the ν(Co−O) vibration in 2 is even lower than in the [(L)CuO] + complexes (L=CH 3 CN, phen, 1,10‐phenanthrenequinone), where the metal‐oxo bonding varies between copper(I)‐oxygen (Cu I O .. ) and copper(II)‐oxyl (Cu II O −. ) configurations, depending on the ligand . This showcases the highly destabilizing effect of the tetragonal environment on the metal‐oxo bonding in 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Markedly, the frequency of the ν(Co−O) vibration in 2 is even lower than in the [(L)CuO] + complexes (L=CH 3 CN, phen, 1,10‐phenanthrenequinone), where the metal‐oxo bonding varies between copper(I)‐oxygen (Cu I O .. ) and copper(II)‐oxyl (Cu II O −. ) configurations, depending on the ligand . This showcases the highly destabilizing effect of the tetragonal environment on the metal‐oxo bonding in 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Also, aspects of the intriguing electronic structure of [CuO] and its role in the gas‐phase reaction with CH 4 has been recently addressed by employing the “tagging” technique . It was shown that bare [CuO] + has prevailingly a copper(I)‐biradical oxygen character.…”
Section: Probing Other Highly Reactive Gas‐phase Speciesmentioning
confidence: 99%
“…It was shown that bare [CuO] + has prevailingly a copper(I)‐biradical oxygen character. Upon ligation with CH 3 CN the electronic structure is better described as that of a copper(II)‐oxyl radical …”
Section: Probing Other Highly Reactive Gas‐phase Speciesmentioning
confidence: 99%
“…Theb onding p(CoÀO) orbitals are now dominantly Co-based do rbitals,w hile the antibonding p*(CoÀO) orbitals are O-based po rbitals.T herefore,t he frontier molecular orbitals are no longer cobalt-based but instead oxygen-based, with the electronic configuration being (d xy ) 2 -(p x (O)) 2 (p y (O)) 1 d z 2 ðÞ 0 d x 2 Ày 2 ÀÁ 0 .T hus,the bonding situation in the doublet complex 2 is best formulated as the Co III center bound to the oxyl group (OC À )w ith the unpaired electron in aporbital perpendicular to the CoÀOa xis.T his cobalt(III)oxyl bonding with as hallow Co À Op otential ( Figure S9) is consistent with the low experimentally observed n(Co À O) stretching frequency. [43] This showcases the highly destabilizing effect of the tetragonal environment on the metal-oxo bonding in 2.I nc onclusion, the low-frequency n(CoÀO) vibration, the characteristic ligand vibrations,a nd the multireference calculations indicate that the ground spin state of 2 is doublet. [43] This showcases the highly destabilizing effect of the tetragonal environment on the metal-oxo bonding in 2.I nc onclusion, the low-frequency n(CoÀO) vibration, the characteristic ligand vibrations,a nd the multireference calculations indicate that the ground spin state of 2 is doublet.…”
Section: Angewandte Chemiementioning
confidence: 77%
“…Markedly,t he frequency of the n(Co À O) vibration in 2 is even lower than in the [(L)CuO] + complexes (L = CH 3 CN,p hen, 1,10-phenanthrenequinone), where the metal-oxo bonding varies between copper(I)oxygen (Cu I OCC)and copper(II)-oxyl (Cu II O À C)configurations, depending on the ligand. [43] This showcases the highly destabilizing effect of the tetragonal environment on the metal-oxo bonding in 2.I nc onclusion, the low-frequency n(CoÀO) vibration, the characteristic ligand vibrations,a nd the multireference calculations indicate that the ground spin state of 2 is doublet. We note that while all experimental and theoretical results are consistent and indicate the same spin assignments,none of the experimental results shows the spin state of the investigated complexes directly.T herefore, corroborating measurements such as EPR spectroscopy would be desirable once it is possible to prepare these complexes in the condensed phase.…”
Section: Angewandte Chemiementioning
confidence: 77%